Impact of the Metal Centre and Functionalization on the Mechanical Behaviour of MIL‐53 Metal–Organic Frameworks. Issue 27 (4th July 2016) - Yot, Pascal G.; Yang, Ke; Guillerm, Vincent; Ragon, Florence; Dmitriev, Vladimir; Parisiades, Paraskevas; Elkaïm, Erik; Devic, Thomas; Horcajada, Patricia; Serre, Christian; Stock, Norbert; Mowat, John P. S.; et al.
Abstract : An extended series of MIL‐53(M)_X metal–organic frameworks (MIL = Materials of Institute Lavoisier; M = Al, Cr, Fe, Sc; X = Cl, CH3, NO2 ) have been systematically investiaged to explore the impact of the nature of both the metal centre and the functions grafted on to the organic linker on the mechanical behaviour of this family of highly flexible hybrid porous frameworks under the application of an external pressure of up to 3 GPa. The high‐pressure X‐ray diffraction measurements allowed the characterization of the pressure‐induced phase transitions of the hydrated structures, the associated volume changes/pressure transitions, and their mechanical resilience through the determination of their bulk moduli. Abstract : The pressure‐induced phase transitions of a series of hydrated MIL‐53 metal–organic frameworks and their compressibility have been investigated as a function of the nature of both the metal centre and the functions grafted on to the organic linker.